(untitled) (LACCEI, 2024)
The main objective of the following research was to determine the relationship between financial education and the entrepreneurial spirit of artisans in the district of Moche in 2022, for which a quantitative study of applied type and non-experimental design with correlational scope was developed. A questionnaire was used as a data collection instrument. The population studied consisted of 34 artisan entrepreneurs who responded to the surveys. The results showed that both variables do have a relationship, as does the financial skills dimension with respect to entrepreneurship. On the other hand, the dimensions financial knowledge, financial attitudes and the entrepreneurship variable have no relationship. It was concluded that there is a relationship between the variables financial education and entrepreneurship and that approximately 8 to 9 out of ten artisans showed a high level of financial education and entrepreneurship.